Computational studies suggest compounds restoring function of p53 cancer mutants can bind SARS-CoV-2 spike protein. Issue 8 (24th May 2023) - Das, Tanushree; Mukhopadhyay, Chaitali
Abstract: It is reasonable to think that cancer patients undergoing chemotherapy or immunotherapy may have a more aggressive course if they are positive for the novel coronavirus disease. Their compulsive condition requires investigation into effective drugs. We applied computational techniques to a series of compounds known for restoring the function of p53 cancer mutant p53 R175H and p53 G245S . Two potent inhibitors, 1-(3-chlorophenyl)-3-(1, 3 -thiazol-2-yl) urea (CTU, PubChem NSC321792) with the highest binding affinity −6.92 kcal/mol followed by a thiosemicarbazone compound N'-(1-(Pyridin-2-yl)ethylidene) azetidine − 1 -carbothiohydrazide (NPC, PubChem NSC319726) with −6.75 kcal/mol were subjected to Molecular Dynamics simulation with receptor binding domain (RBD) and compared with control ligand dexamethasone. In particular, CTU adheres to pocket 1 with an average free energy of binding −21.65 ± 2.89 kcal/mol at the RBD - angiotensin-converting enzyme 2 binding region with the highest frequency of amino acid residues after reaching a local equilibrium in 100 ns MD simulation trajectory. A significant enthalpy contribution from the independent simulations unfolds the possibility of dual binding sites for NPC as shifted pocket 1 (−15.59 ± 5.98 kcal/mol) and pocket 2 (−18.90 ± 5.02 kcal/mol). The obtained results for these two compounds are in good agreement with dexamethasone (−18.45   ± 2.42 kcal/mol). Taken together our findings could facilitate the discovery of small molecules that restore the function of p53 cancer mutants newly against COVID-19 in cancer patients. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001